The Living Standards, Incomes and Accommodation Costs of Older New Zealanders Revisited - Roger Hurnard; Dean Hyslop; Ivan Tuckwell (New Zealand Government, The Treasury, 2005)
In 2001 the then Ministry of Social Policy published a comprehensive study of the living standards of older New Zealanders. The current paper revisits the estimated relationship between material well-being and the current income and accommodation costs of older people, and questions the extent to which income and accommodation costs directly affect well-being or proxy for other factors. We first extend the estimated relationship between material well-being and current income to include the source of the income as well as its level. We find that controlling for different income sources roughly halves the estimated associative effect of income on material well-being. Furthermore, for a given level of income, those with higher fractions of either employment earnings or capital investment income have significantly higher material well-being scores, while those with a higher fraction of income from benefit allowances have lower scores. One interpretation is that these factors may proxy for other causal factors, such as health and wealth effects, rather than reflecting a direct income effect. Next, we extend the original specification between material well-being and accommodation costs to, first, include property rates as an accommodation cost and, second, to control for the type of housing tenure (freehold homeowner, mortgaged, renter, and no accommodation costs). We find that, controlling for housing tenure, the estimated effect of accommodation costs (including rates) is, at most, half that originally estimated and, for some specifications, insignificantly different from zero. Furthermore, controlling for the level of accommodation costs, mortgage holders and renters have significantly lower material well-being scores than freehold homeowners. These findings suggest that understanding what influences the material well-being outcomes of older people is not as straightforward as might be suggested by the simple association of certain variables.
Keywords: I32; 330; Living standards; material well-being; current income; accommodation costs